Do Crowding-Out Effects Explain the Low Effect of a Health Promotion Intervention among Young People at a Vocational School? - Bent E. Mikkelsen (MDPI AG, 2021)
In recent years, school-based interventions have increasingly been used as a strategy to promote good eating habits and physical activity among young people at school. However, little is known about the effect that this kind of public involvement has on the overall behavior of young people. Economists refer to the existence of a crowding-out effect when public sector engagement in influencing behavior is counteracted by behaviors at the individual level. The aim of this study was to investigate the effects of a health promotion intervention program among young people at a vocational school on the overall behavior of the students and consider whether a crowding-out effect existed when it came to health behavior. This study used data from the Gearing up the Body (GUB) intervention that was carried out at the vocational school of Uddannelsescenter Holstebro, Denmark. The study included 130 students from two vocational programs. Answers were collected from survey questions in three waves. Our results showed that intervening in the school setting had the intended impact on physical activity but an unintended impact on eating behavior. In the GUB study, we found signs of countervailing behaviors in and out of school that need to be further explored.